Atypical spindle cell lipomatous tumor of the tongue: A rare entity arising in an unusual location. Issue 8 (11th August 2022) - Graja, Soumaya; Chaari, Chiraz; Kammoun, Chahir; Zghal, Mouna; Dhouib, Morched; Charfi, Slim; Sellami‐Boudawara, Tahya
Abstract: Atypical spindle cell/pleomorphic lipomatous tumor (ASCPT) constitutes an emerging entity of lipomatous tumors. It is a benign tumor. It occurs typically in limbs and limb girdles. The occurrence in oral cavity is unusual. The diagnosis of this neoplasm is challenging. Herein, we report a case of ASCPT arising in the tongue. Abstract : ASCPT is a benign adipocytic neoplasm characterized by the presence of adipocyte cells, lipoblast cells, spindle cells at varying degrees, and a myxoid or collagenous extracellular matrix. Local recurrence is rare but there is no risk for dedifferentiation. The occurrence in the oral cavity and in the tongue is exceptional. The diagnosis in this localization is challenging. The patient has generally an excellent prognosis after a complete excision.